Graphene and Other 2D Layered Nanomaterials and Hybrid Structures: Synthesis, Properties and Applications - Cesano, Federico; Scarano, Domenica (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
ResearchGate academic profile and social networking site for researchers: "Graphene, one of the most interesting and versatile materials of modern times, is recognized for its unique properties, which are strongly different from its bulk counterpart. This discovery has recently stimulated research on other two-dimensional (2D) systems, all consisting of a single layer of atoms. Two-dimensional materials have also emerged as major candidates for use in next-generation applications as a result of the rapid discovery of their any properties. In this Special Issue, we have collected a few recent studies that examine some of these new areas of work in the field of 2D materials."